Effect of Tinospora cordifolia and Ascorbic Acid Supplementation on Biochemical Parameters of Broiler Chickens - Jain, D.; Dhuria, R. K.; Sharma, T.; Bothra, T.; Prajapat, Umesh Kumar (International Journal of Livestock Research, 2020)
A 42 days feeding trial was carried out to investigate the effect of Tinospora cordifolia (at graded levels) or ascorbic acid alone and in combinations on biochemical parameters using 360 one-day-old broiler chicks in 5×2 factorial experiment within a completely randomized design and divided into ten (10) dietary treatments groups (T1-T10) in triplicate of twelve chicks per replicate. The average temperature (31oC) during the research trial was higher than the recommended normothermia zone i.e. 18-24°C established for poultry birds, which indicated that poultry birds were in heat stress. Improvement in various biochemical parameters of broilers was observed due to supplementation of ascorbic acid or Tinospora cordifolia (Geloi) alone and in combination. Supplementation of ascorbic acid or Tinospora cordifolia (Geloi) may exert positive response on health status of broilers during chronic heat stress.